PERUSAHAAN ASURANSI JIWA KONVENSIONAL DAN PERUSAHAAN ASURANSI JIWA SYARIAH (SUATU ANALISIS PERBANDINGAN) - Zahara, Neni; Saputra, Mulia (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
The purpose of this study is to measure the efficiency of conventional and sharia life insurance companies in indonesia during the period 2012-2016 and to find out whether there are differences in efficiency between conventional and sharia life insurance companies. This research is a quantitative descriptive research using secondary data sourced from the company's annual financial statements. The samples used were 10 conventional life insurance companies and 10 sharia life insurance companies. Efficiency measurement in this study uses the Data Envelopment Analysis (DEA) method with an value-added approach. The input variables used are assets, capital, general and administrative costs, and commission expenses. While the output variable is premium and investment income. The results of this study indicate that conventional life insurance companies have a better level of efficiency than sharia life insurance companies, but there is no significant efficiency difference between conventional life insurance companies and sharia life insurance companies during the 2012-2016 period.